Kajian dinamika populasi ikan kepek, Mystacoleucus obtusirostris (Valenciennes, in Cuvier & Valenciennes 1842) di Sungai Opak Yogyakarta - Djumanto Djumanto; Maria Intan Permata Devi; Ilma Fatimah Yusuf; Eko Setyobudi (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2014)
The Mystacoleucus obtusirostris is one of the main species of fish caught in Opak River. The study of population dynamics is important as the basis tools for fisheries management in order the stocks of kepek fish can be exploited in a sustainable manner. The purpose of the study was to examine the population parameters of M. obtusirostris inhabitat in the Opak River of Yogyakarta, namely growth and mortality rate, and recrutment pattern. Fish sampling was done by sampling once a week in May-July 2012 and every two weeks in February-April 2013, respectively. Fish sampling was conducted using electrofishing operated by local fishermen. All samples of kepek fish were collected and measured the total length using a metal ruler, and weighted individually using digital scales. Length frequency data were analyzed using the software FiSAT II to estimate parameters of growth, mortality, and recruitment. The results showed the growth parameters of VBGF, namely L<», K, and to was 18.9 cm, 0.75 per year and -0.21, respectively, while the growth performance (0 ') was 2.43. The total mortality was 2.19 per year, natural mortality and fishing mortality was 1.71 and 0.48 per year, respectively, as well as the exploitation rate was 0.21. The spawning was estimated occured in October coincided with the starting of the rainy season, meanwhile the recruitment into fishing ground was occurred monthy starting from Januari with peaking in June year. Abstrak Ikan kepek (Mystacoleucus obtusirostris) merupakan salah satu jenis ikan tangkapan utama di Sungai Opak. Kajian dinamika populasi menjadi sangat penting sebagai dasar pengelolaan perikanan agar stok ikan kepek dapat dimanfaatkan secara berkelanjutan. Penelitian ini bertujuan untuk mengkaji laju pertumbuhan, mortalitas, dan pola rekrutmen ikan ke-pek di Sungai Opak Yogyakarta. Pengambilan contoh ikan dilakukan pada bulan Mei-Juli 2012 dan Februari-April 2013, dengan menggunakan alat kejut yang dioperasikan oleh nelayan setempat. Semua contoh ikan kepek yang ter-tangkap diukur panjang total menggunakan mistar logam dan berat individu menggunakan timbangan digital. Data fre-kuensi panjang dianalisis menggunakan perangkat lunak FiSAT II untuk menduga parameter pertumbuhan dan mortalitas. Hasil penelitian menunjukkan parameter pertumbuhan VBGF L„ (18,9 cm), K (0,75), dan to (-0,21 tahun), sedangkan performa pertumbuhan (0’) adalah 2,43. Mortalitas total 2,19 per tahun, mortalitas alami 1,71 per tahun, mortalitas penangkapan 0,48 per tahun, dan tingkat eksploitasi sebesar 0,21. Pemijahan diperkirakan terjadi pada bulan Ok-tober bertepatan awal musim penghujan, sedangkan rekrutmen ke daerah tangkapan terjadi setiap bulan mulai Januari dengan puncaknya pada Juni saat musim kemarau.